Classical and alternate complement factor overexpression in non-obese weight matched women with polycystic ovary syndrome does not correlate with vitamin D - Moin, Abu Saleh Md; Sathyapalan, Thozhukat; Butler, Alexandra E.; Atkin, Stephen L. (Frontiers in Endocrinology, 2022)
Introduction. Women with polycystic ovary syndrome (PCOS) exhibit complement factor expression changes that may be obesity-driven rather than an intrinsic facet of PCOS; furthermore, complement changes have been associated with vitamin D deficiency, a common feature of PCOS. Therefore, complement pathway proteins and vitamin D levels may be linked in PCOS. Methods. We measured plasma levels of complement pathway proteins by Slow Off-rate Modified Aptamer (SOMA)-scan plasma protein measurement for the classical (C4, C4a, C4b) and alternative pathways (C3, C3b, iC3b, properdin, factors B, D, H) in weight and aged-matched non-obese non-insulin resistant women with PCOS (n=24) and control women (n=24). Proteins that differed between groups were correlated to 25-hydroxyvitamin D3 (25(OH)D3) and 1,25-dihydroxyvitamin D3 (1,25(OH)2D3), measured by isotope-dilution liquid chromatography tandem mass spectrometry. Results. Women with PCOS had a higher free androgen index and anti-mullerian hormone, though insulin resistance was comparable to controls; likewise, C-reactive protein, a marker of inflammation, was comparable between cohorts. In the alternative complement pathway, C3, iC3b and properdin were increased in PCOS (p<0.05), whilst C4 in the classical pathway was increased (p<0.05). 25(OH)D3 levels positively correlated with C3b only in control subjects, with no correlation of 1,25(OH)2D3 with any of the proteins. Conclusion. In a non-obese PCOS population matched for age, insulin resistance and inflammation, initiating proteins of the classical and alternate complement cascades were increased. However, a positive correlation with 25(OH)D3 was only seen for C3b in control subjects, with no correlation to 1,25(OH)2D3, suggesting that the increase in complement proteins in PCOS is vitamin D-independent.